The Effect of Liquid Organic Fertilizer Made from Catfish Waste on the Biomass of Lemna sp in the Maintenance Media of Kissing Gourami (Helostoma temminckii) on Peat Water - Nurhadi, Mhd Ilham; Syafriadiman, Syafriadiman; Hasibuan, Saberina (Jurnal Natur Indonesia, 2025)
Peat water is acidic and nutrient-poor, thus less supportive for aquatic organisms. Lemna sp. has potential as both a phytoremediator and natural feed, but its growth depends on nutrient availability. Catfish waste can be fermented into liquid organic fertilizer (POC), rich in nitrogen, phosphorus, and potassium. This study aimed to examine the effect and optimal dosage of catfish-waste POC on the biomass of Lemna sp in peat water used for rearing kissing gourami (Helostoma temminckii). The research was conducted for 30 days, from March to April 2025, at the Environmental Quality Laboratory of Aquaculture, Faculty of Fisheries and Marine, Universitas Riau. The experimental method used a Completely Randomized Design (CRD) with five treatments and three replications. The treatments were: P0 (control, without POC), P1 (1.75 mL/L), P2 (2.0 mL/L), P3 (2.25 mL/L), and P4 (2.5 mL/L). The best result was obtained in treatment P3 (2.25 mL/L), with water quality values of temperature 26–30.4℃, pH 3.8–7.2, dissolved oxygen 4.54–7.37 mg/L, nitrate 0.39–15.86 mg/L, phosphate 3.06–6.05 mg/L, and CO₂ 5.0–10.0 mg/L. This treatment also produced a biomass increase of Lemna sp. of 107.6 g and a specific growth rate of 5.05%.